1971
DOI: 10.1111/eci.1971.1.4.216
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic Modification of Glucose‐Induced Biphasic Insulin Release from Perifused Rat Pancreas

Abstract: Immediate and deferred effects of agents stimulating or inhibiting α or β adrenergic receptors have been studied in a perifusion preparation of rat pancreas in which glucose induces a biphasio pattern of IRI release. Epinephrine directly inhibited both the primary and the secondary phases of IRI release during the period of glucose stimulation. Propranolol inhibited only the secondary response. Low concentrations of isoproterenol stimulated, yet high concentrations inhibited both primary and secondary glucose‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

1974
1974
1985
1985

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 36 publications
4
21
0
Order By: Relevance
“…These observations, about acute responsiveness of the bursa-derived cell to AcCh and the apparent presence of reflex pathways, have potential significance in that there appears to be a "delay" in insulin release in diabetics (38)(39)(40). These results may also be considered in light of previous data suggesting that while both phases of glucose induced insulin release may be influenced by similar agents, there are differences, at least in emphasis, in the major mechanisms through which these phases are generated (12,19,29,41,42). Thus, it is observed that while muscarinic agents can stimulate biphasic insulin release in the presence of glucose, it is evident that the dose-response relationships are different for the two phases.…”
Section: As Indicated Inmentioning
confidence: 76%
See 4 more Smart Citations
“…These observations, about acute responsiveness of the bursa-derived cell to AcCh and the apparent presence of reflex pathways, have potential significance in that there appears to be a "delay" in insulin release in diabetics (38)(39)(40). These results may also be considered in light of previous data suggesting that while both phases of glucose induced insulin release may be influenced by similar agents, there are differences, at least in emphasis, in the major mechanisms through which these phases are generated (12,19,29,41,42). Thus, it is observed that while muscarinic agents can stimulate biphasic insulin release in the presence of glucose, it is evident that the dose-response relationships are different for the two phases.…”
Section: As Indicated Inmentioning
confidence: 76%
“…This method provides an accurate assessment of the total amount of insulin released in the second phase, as confirmed in this and in previous studies, by measuring the insulin content of all the perifusate collected over the appropriate period (12,19). For those studies that exhibited flat responses, phases were arbitrarily defined by reference to appropriate matching experiments (12,19). Statistics used either the Wilcoxon rank test and/or the Student t test.…”
Section: Methodsmentioning
confidence: 85%
See 3 more Smart Citations